RESEARCH FINDINGS AND IMPLEMENTATION CHALLENGES OF THE CONTINUING PROFESSIONAL DEVELOPMENT (CPD) POLICY FOR THE SOCIAL WORK PROFESSION IN SOUTH AFRICA - Lombard, Antoinette (Social Work/Maatskaplike Werk, 2010)
The principled decision taken by the South African Council for Social Service Professions (SACSSP) in July 2003, effective from 1 April 2010, was to adopt continuing professional development (CPD) as a requirement for practising social work. The decision was based on a widely consultative process, which had commenced early in 2001, continuing through various phases and drafts, and culminating in the final CPD policy in July 2009 (Lombard, Pruis, Grobbelaar & Mhlanga, 2010).